Is Social Capital an Effective Director Attribute? An Empirical Analysis of Board of Directors’ Social Connectivity and its Contribution to New Zealand Stock Exchange Firms - Andersen, Angela (Auckland University of Technology, 2019)
Corporate directors are required to have an adequate set of capabilities to meet an increasingly diverse range of board responsibilities. Social capital, the value that resides in relationships with others, is an attribute that can support firms by assisting directors in directing and advising management. An important source of social capital that directors bring to the boardroom is their connections to other directors. This connectivity allows directors to access other board members’ skills, knowledge, and experiences. In particular, networks of directors facilitate the sharing of greater amounts of timely and business-relevant information. However, the prevailing literature has not been able to provide a consistent answer as to the value of social connectivity. This thesis investigates whether social capital is an important director attribute by employing Social Network Analysis. Using a hand-collected dataset of directors, we contribute to the finance literature by providing new empirical evidence on the value of social capital for New Zealand listed firms. This thesis consists of three empirical studies that collectively provide evidence on the value of social capital for directors and firms. First, we examine the determinants of social capital. We find a positive and significant relationship between human capital and social capital which suggests that human capital needs to be controlled for when examining the importance of connectivity. To date, this issue has not been well considered in previous studies. Second, we study whether connectivity is conducive to board appointments by investigating the value that firms and shareholders place on social capital. The results suggest that social capital positively influences the director selection process, above and beyond human capital. We find that directors who are more connected, receive more board appointments because of their higher social capital. However, we also document that there is no significant abnormal market reaction to firms that appoint well-connected directors. This finding suggests that greater connectivity allows directors to access new board positions despite not necessarily contributing to shareholder value. Third, we find that social capital improves firm performance, although this relationship is non-linear whereby the benefit of connectivity decreases if boards become far too connected. We also find that poorly performing firms achieve greater benefits from connectivity than firms already performing well. We further document that social capital has a greater impact on firm performance when there is a greater need for the board’s input.
Keywords: Corporate Governance; Corporate Finance; Social Connectivity; Resource Dependence; Board of Directors; Social Network Analysis; Social Capital; Human Capital; Centrality; Director Appointments